FAKTOR YANG MEMPENGARUHI SISWA MELANGGAR TATA TERTIB DI JURUSAN BANGUNAN SMK NEGERI 1 PADANG - 1965-1981 , Faisal Murnawan Amin (CIVED, 2016)
ABSTRACK This research is descriptive with quantitative approach. The purpose of this research was to uncover the factors which led to students a foul in the building department of SMK Negeri 1 Padang.The population of this researc was all students in grade XI and XII in the building department of SMK Negeri 1 Padang with total population is 206 people. Samples in this research is 136 people. Instrument of this research is questionnaire with the number of requests is 43 items. The result of this reseach is factors affecting students disciplinary breances in building department of SMK Negeri 1 Padang are physical condition/Health, emotional, mental,  community, school environment, economy, dan social. The most dominant factors influencing student discipline violations are emotional, environment, dan school environment. Key Word : Violation, code of conduct